REHABILITATION OUTCOMES IN ARTHROGRYPOSIS MULTIPLEX CONGENITA - Sibel Özbudak Demir; Z. Aydan Kurtaran; Füsun Köseoğlu; Müfit Akyüz (Archives of Rheumatology, 2002)
Arthrogryposis Multiplex Congenita is a non progressive syndrome which is characterized by multiple joint contractures. Its etiology has been unknown. Viral infections and autosomal dominant transitions have been blamed for it. The aim of the study was to evaluate clinic and demographic characteristics and to investigate the progress of joint limitations and ambulation ability during rehabilitation. Prenatal, natal, postnatal features and progresses of the patients involved in this study have been noted. The localication and degree of the joint contractures been identified. Their ambulation ability and treatment applied have been assessed. The average age of the patients (7 male, 3 female) was 5,72±3,43. The length of stay at the rehabilitation center was 72,23±0,22 days. Breech presentation in 6 (%60) of the patients was established. 4 (%40) of the patients had congenital hip dislocation and 3 (%30) of them had genital anomaly. The joints in which contracture were the most frequenty localized were knee (%90), ankle (%80) and hip (%70) joints. At the end of the rehabilitation programme passive range of motion and ambulation degree increased.